MY BEAUTIFUL CITY KHOJELI - Saylaovna, Kenjebayeva Roza (PT. Antis International Publisher, 2024)
Poet Rakhmet Ayapbergenov was born in Katep settlement of Khozheli district of the Republic of Karakalpakstan, where his poetic inspiration was awakened. The poet spent his childhood in Katep. A young boy who grew up surrounded by the beautiful nature of his native village and rolled in the sand of Chandak writes several poems dedicated to his native land with the passion of his youth. The paper-yellow boy who flew from the village of Ayadai with his wings would always speak of his native village with pride. Poems dedicated to the motherland are philosophically loved by their readers. In the poet's poems, there is love for the native land, motherland, love, morality and loyalty